Salivary peroxidase levels in patients with oral ulcerative lichen planus - MR Salehi; A Tavangar; H Khademi; AR Mohammadi (Isfahan University of Medical Sciences, 2010)
Introduction: Oral Lichen Palnus (OLP) is a well clinically and histologically described chronic mucocutaneous disease with unknown etiology. A large number of both systemic and local predisposing factors have been implicated in the pathogenesis of OLP. Saliva and its constituents are considered to play an important role in the homeostasis of the oral cavity and therefore any alterations in their quantity or quality may give rise to various oral diseases. The aim of this study was to evaluate the salivary peroxidase levels in patients with oral ulcerative lichen planus.Materials and Methods: in this case-control study, a total of twenty patients with OLP (mean age 35.4 years) were included in the case group. The same number of normal healthy individuals (mean age 39.3 years) were put into the control group. Subjects collected their saliva between 8-10 am using the simple method of unstimulated spitting. Saliva samples were collected into calibrated tubes (0.1 ml) during a five minute period. Salivary peroxidase level was checked based on Putter and Becker method. The data were analyzed in SPSS using t-student test (α = 0.05).Results: The mean ± SD salivary peroxidase levels were 3.59 ± 0.71 and 3.69 ± 0.74 in the case and control groups, respectively. The difference between the two groups was not statistically significant (p value = 0.669).Conclusion: Within limitation of the present study, salivary peroxidase level does not seem to have a role in the pathogenesis of OLP. Key words: Peroxidase, Saliva, Oral lichen planus.